Association Between Metabolic and Hormonal Derangements and Professional Exposure to Urban Pollution in a High Intensity Traffic Area - Molfino, Alessio; Amabile, Maria Ida; Muscaritoli, Maurizio; Germano, Annunziata; Alfano, Rossella; Ramaccini, Cesarina; Spagnoli, Alessandra; Cavaliere, Liberato; Marseglia, Gianluca; Nardone, Antonio; Muto, Giuseppina; Carbone, Umberto; et al. (Frontiers in Endocrinology, 2020)
Rationale: Studies suggest a relation between exposure to air particulate matter (PM)2.5 pollution and greater cardiovascular morbidity, as well as increased risk for obesity and diabetes. We aimed to identify association(s) between nutritional and metabolic status and exposure to environmental pollution in a cohort of policemen exposed to high levels of air pollution. Methods: We considered adult municipal policemen, working in an urban area at high-traffic density with documented high levels of air PM2.5 (exposed group) compared to non-exposed policemen. Clinical characteristics, including the presence/absence of metabolic syndrome, were recorded, and serum biomarkers, including adiponectin, leptin, and ghrelin, were assessed. Results: One hundred ninety-nine participants were enrolled, 100 in the exposed group and 99 in the non-exposed group. Metabolic syndrome was documented in 32% of exposed group and in 52.5% of non-exposed group (P = 0.008). In the exposed group, we found a positive correlation between body mass index and serum leptin as well as in the non-exposed group (P < 0.0001). Within the exposed group, subjects with metabolic syndrome showed lower serum adiponectin (P < 0.0001) and higher leptin (P = 0.002) levels with respect to those without metabolic syndrome, whereas in the non-exposed group, subjects with metabolic syndrome showed only higher leptin levels when compared to those without metabolic syndrome (P = 0.01). Among the participants with metabolic syndrome, we found lower adiponectin levels in those of the exposed group with respect to the non-exposed ones (P = 0.007). When comparing the exposed and non-exposed groups, after stratifying participants for Homeostatic Model Assessment for Insulin Resistance >2.5, we found lower adiponectin levels in those of the exposed group with respect to the non-exposed ones (P = 0.038). Conclusions: Exposure to air PM pollution was associated with lower levels of adiponectin in adult males with metabolic syndrome.